Effects of Wannachawee Recipe with Antipsoriatic Activity on Suppressing Inflammatory Cytokine Production in HaCaT Human Keratinocytes - Takuathung M. (2017)
© 2017 Mingkwan Na Takuathung et al. Psoriasis is a chronic inflammatory and immune-mediated skin disease. The pathogenesis involves T cells activation via the IL-23/Th17 axis. Conventional treatments of psoriasis have adverse events influencing patients' adherence. Wannachawee Recipe (WCR) has been effectively used as Thai folk remedy for psoriasis patients; however, preclinical evidence defining how WCR works is still lacking. This study defined mechanisms for its antiproliferation and anti-inflammatory effects in HaCaT cells. The cytotoxicity and antiproliferation results from SRB and CCK-8 assays showed that WCR inhibited the growth and viability of HaCaT cells in a concentration-dependent manner. The distribution of cell cycle phases determined by flow cytometry showed that WCR did not interrupt cell cycle progression. Interestingly, RT-qPCR revealed that WCR significantly decreased the mRNA expression of IL-1β, IL-6, IL-8, IL-17A, IL-22, IL-23, and TNF-α but induced IL-10 expression in TNF-α- and IFN-γ-induced HaCaT cells. At the protein level determined by ELISA, WCR significantly reduced the secretion of IL-17A, IL-22, and IL-23. The WCR at low concentrations was proved to possess anti-inflammatory effect without cytotoxicity and it did not interfere with cell cycle of keratinocytes. This is the first study to provide convincing evidence that WCR is a potential candidate for development of effective psoriasis therapies.